The Role of Cytoskeletal Proteins in the Regulation of Mitochondrial Function - Andrey V. Kuznetsov; Sabzali Javadov; Michael J. Ausserlechner; Judith Hagenbuchner (Recent Research Advances in Biology Vol. 8, 2021)
Identification of the mitochondrial roles and regulatory mechanisms for the understanding of muscle bioenergetics is a fundamental problem in physiology/pathophysiology. The three cytoskeletal systems microtubules, intermediate filaments, and microfilaments play a fundamental role in the maintenance of mitochondrial structure/architecture, intracellular organization and motility. Moreover, numerous communications between cytoskeleton and mitochondria can actively contribute to the regulation of mitochondrial respiratory function and oxidative phosphorylation (OXPHOS). In skeletal and cardiac muscles, mitochondrial positions are firmly fixed with very regular arrangement along filaments, providing a basis for many interactions with cellular systems such as cytoskeleton and sarcoplasmic reticulum (SR). Importantly, this might involve association of cytoskeletal elements with VDAC (the voltage-dependent anion channel), by this means, controlling the permeability of the outer mitochondrial membrane (OMM) and overall mitochondrial energy metabolism. Cardiac muscles and isolated cardiomyocytes show also a regular arrangement of tubulin beta-II fully co-localized with mitochondria, in contrast to other tubulin isoforms. This finding suggests the participation of tubulin beta-II in the regulation of OMM permeability through interaction with VDAC. In addition, the OMM permeability might be regulated by the specific isoform of cytoskeletal protein plectin. This book chapter summarizes and discusses previous studies on the role of cytoskeleton in the regulation of energy metabolism and mitochondrial physiology, OXPHOS and intracellular energy transfer.